1989
DOI: 10.1111/j.1467-8489.1989.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic Optimisation of Sprinkler Irrigation Considering Uncertainty of Spatial Water Distribution*

Abstract: The sNdy is focused on the development and the application of a stochastic economic optimisation model by which optimal levels of applied water and sprinkler spacing are determined. Data on cropwater production function and uniformity of water application are taken from a sprinkler irrigation plot of sweet corn. It was found that a saving of irrigation water can be achieved not only by raising water prices but also by increasing application uniformity. The spatial variability of applied irrigation water has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…92 and 12%, respectively, parallel to the MSIS spans, and 0.89 and 14%, respectively, perpendicular to the MSIS (Table 1). Feinerman et al (1989) found that nonuniform water application with CV < 15% had negligible effect on crop yield.…”
Section: Resultsmentioning
confidence: 93%
“…92 and 12%, respectively, parallel to the MSIS spans, and 0.89 and 14%, respectively, perpendicular to the MSIS (Table 1). Feinerman et al (1989) found that nonuniform water application with CV < 15% had negligible effect on crop yield.…”
Section: Resultsmentioning
confidence: 93%